Imperialist Japan : - Montgomery, Michael (Christopher Helm, 1987)
A study of Japanese imperialism, in its historical context, focusing on underlying psychological factors: the sense of inferiority engendered by wholesale adoption of Chinese culture, the long period of isolation, the hierarchical nature of the society, and Japan's present economic strength